Clinical heterogeneity of diffuse large B cell lymphoma following failure of front‐line immunochemotherapy. (27th June 2017) - Farooq, Umar; Maurer, Matthew J.; Thompson, Carrie A.; Thanarajasingam, Gita; Inwards, David J.; Micallef, Ivana; Macon, William; Syrbu, Sergei; Lin, Tasha; Lin, Yi; Ansell, Stephen M.; Nowakowski, Grzegorz S.; et al.
Summary: This study aimed to describe the patterns of care and outcomes of diffuse large B cell lymphoma (DLBCL) after failure of front line anthracycline‐based immunochemotherapy (IC). Patients with newly diagnosed lymphoma were prospectively enrolled in Molecular Epidemiology Resource (MER) of the University of Iowa/Mayo Clinic Lymphoma Specialized Program of Research Excellzence. All DLBCL and primary mediastinal B‐cell lymphoma (PMBL) patients treated with front‐line anthracycline‐based IC were followed for relapse. Patients with relapse on follow‐up and subsequently retreated were included in this analysis. 1039 patients received anthracycline‐based IC between 2002 and 2012, of which 244 relapsed and were subsequently retreated. Across all therapies, overall survival at 4 years (OS4) from relapse was 28% and 103 patients ultimately underwent autologous haematopoietic cell transplant (autoHCT) with OS4 from autoHCT of 51%. Patients relapsing after 12 months from initial diagnosis had OS4 of 47% but those with a transient or no response to initial therapy had OS4 of only 13%. Outcomes of relapsed or refractory DLBCL differ substantially when categorized by response to initial therapy, timing of relapse and opportunity to undergo autoHCT. The design and interpretation of uncontrolled trials should account for this heterogeneity in patients with relapsed DLBCL.